Analysis of Stock Intrinsic Value and Projection of Financial Statements through a fundamental analysis approach to PT. Fast Food Indonesia, Tbk in 2022. - Wulandari, Futri Ayu (Kirana Publisher (KNPub), 2023)
This study aims to determine the intrinsic value of PT. Fast Food Indonesia, TBK using the residual profit valuation model which can determine the value of equity at that time as the sum of the current book value and the present value of the estimated residual income in the future. This study uses a descriptive quantitative approach in presenting the results of the analysis. The data source in this study is the annual financial report of PT. Fast food Indonesia, Tbk in 2021 and 2022. Data collection techniques in this study used observation and documentation techniques. This research shows that the result of the projection is the intrinsic value of PT. Fast Food Indonesia Tbk in 2022 is Rp. 1.70 which was found based on the calculation of the prospective analysis in the residual profit valuation model (Residual Income Model). It was recorded that until the end of December 2022 the share price of PT. Fast Food Indonesia, Tbk is Rp. 820. So it can be concluded that the value of PT. Fast Food Indonesia, Tbk is overvalued or the stock market price is higher than the intrinsic value of the stock. Keywords: Stock instruction value, Financial statement, prospective analysis, financial ratio